Grease - Kleiser, Randal; Travolta, John, 1954-; Newton-John, Olivia; Paramount Pictures Corporation (Hollywood, Calif. : Paramount Pictures, 2001)
A musical about the fabulous 50's. This edition includes retrospective interviews with principal stars, the director and producer.
Title from disc surface.
DVD release of the 1978 film version of the smash hit play.
Special features: Original theatrical trailer, retrospective interviews.
Based on the original musical by Jim Jacobs and Warren Casey ; choreography, Patricia Birch.
John Travolta, Olivia Newton-John, Stockard Channing, Eve Arden, Frankie Avalon, Joan Blondell, Edo Byrnes, Sid Caesar, Alice Ghostley, Dody Goodman, Sha-Na-Na.
Rated PG.
Keywords: High school students -- Drama; Nineteen fifties -- Drama; Feature films; Films for the hearing impaired; Musical films